Extremely fast charging lithium-ion battery using bio-based polymer-derived heavily nitrogen doped carbon. Issue 100 (24th November 2021) - Patnaik, Kottisa Sumala; Badam, Rajashekar; Peng, Yueying; Higashimine, Koichi; Kaneko, Tatsuo; Matsumi, Noriyoshi
Abstract : Heavily nitrogen doped carbon was designed by facile pyrolysis of bio-based poly(2, 5 benzimidazole) as single source of carbon and nitrogen and utilized as extremely fast charging anode in Li-ion batteries. Abstract : Extremely high nitrogen doped carbon was designed by facile pyrolysis of bio-based poly(2, 5-benzimidazole) as a single source of nitrogen and carbon. For the first time ever, a carbon-based anode with ∼17 wt% of nitrogen doping with extremely fast charging (XFC) capability at 18.6 A g −1 and ultralong cyclability (3000 cycles) with 90% capacity retention was investigated. Full cell studies also indicated the commercial competence of the novel material.